2012
DOI: 10.1371/journal.pone.0034187
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Monitoring of Patients Treated with Antihypertensive Drugs and Newly Exposed to Non Steroidal Anti-Inflammatory Drugs: A Cohort Study

Abstract: Background Drug-Drug Interactions between Non Steroidal Anti-Inflammatory Drugs (NSAIDs) and Angiotensin Converting Enzyme Inhibitors (ACEIs), Angiotensin Receptor Blocker (ARBs) or diuretics can lead to renal failure and hyperkalemia. Thus, monitoring of serum creatinine and potassium is recommended when a first dispensing of NSAID occur in patients treated with these drugs. Methods We conducted a pharmacoepidemiological retrospective cohort study using data from the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 19 publications
(22 reference statements)
4
11
0
1
Order By: Relevance
“…Moreover, we demonstrated that NSAIDs were less frequently found in older patients exposed to antiplatelet drugs. We found similar results in the cohort of hypertensive patients , suggesting that age and level of cardiovascular risk could be factors leading to less NSAID's prescriptions.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Moreover, we demonstrated that NSAIDs were less frequently found in older patients exposed to antiplatelet drugs. We found similar results in the cohort of hypertensive patients , suggesting that age and level of cardiovascular risk could be factors leading to less NSAID's prescriptions.…”
Section: Discussionsupporting
confidence: 78%
“…We showed that exposure to NSAIDs was no more than 4.5% in patients treated with antihypertensive drugs. This low prevalence could be reassuring, but should be interpreted with caution: We recently demonstrated that in a cohort of patients treated with antihypertensive dugs, the incidence of NSAID's exposure was 25.1/100 person-years [9]. Ketoprofen, diclofenac, ibuprofen, nimesulide, and naproxen were the most commonly prescribed NSAIDs in the population of patients treated with antihypertensive drugs in the present study.…”
Section: Discussionsupporting
confidence: 51%
“…The first situation is when they start any novel drug (prescription or over-the-counter) or find a need to use non-steroidal anti-inflammatory drugs. The reason to do so is that several commonly used drugs (e.g., cotrimoxazole, non-steroidal anti-inflammatory drugs) predispose to hyperkalemia, especially in patients using RAAS-blockers [37,38]. The second situation is in the case of dose adjustments of prescribed drugs (e.g., RAAS-blockers), when the research team will decide whether this justifies earlier monitoring of serum K + through an additional study visit.…”
Section: Methodsmentioning
confidence: 99%
“…Como limitaciones tenemos el reducido número de casos y no haber incluido el tratamiento con AAS a pequeñas dosis (100 y 300 mg) como efecto AINE sino como antiagregante, como así consta en la codificación farmacéutica, ya que gran parte de los pacientes ingresados (19), se encontraban en tratamiento profiláctico con estas dosis. Paracetamol a dosis mayor de 4 g/d, podría también tener un efecto AINE.…”
Section: Conflicto De Interesesunclassified